Organizational confidence among workers in the colleges of education / University of Baghdad (Journal of the College of Basic Education, 2022)
A field study aimed at knowing the degree of organizational trust in the faculties of education at the University of Baghdad, and adopted the descriptive analytical approach. The research community was identified, which consists of (339) managers and administrative employees, and the research sample was chosen in a simple random way, with a percentage of (66.076%) of the research community, as the number of sample members reached (224) managers and workers in colleges. A questionnaire was built that included (60) items distributed among the fields of study. The researcher made sure of its validity and reliability. The research data was analyzed using the (SPSS) program, and the researcher applied the questionnaire in the first semester of the academic year 2014-2015. And I reached results that were analyzed and discussed according to the fields of the organized study, which are trust in the college systems and its leaders, relationships, interest in workers, interest in work and productivity, and empowerment of workers.